The Manasseh hill country survey - Zertal, Adam. (Culture and history of the ancient Near East, 2004)
The book presents the results of a complete and detailed archaeological survey in the area of ancient Shechem and Samaria. This survey is being conducted since 1978, and it relates to some 400 square kilometers of the heartland of the central hill country of Israel/Palestine. It is a detailed and thorough archaeological and historical work, which deals with the most important area for biblical and other researches. This territory and its survey is a most valuable tool for every scholar involved in Bible, theology, Ancient Near Eastern history, and other schools concerned.